The Influence of Altruistic Leadership and Empowering Leadership on Organizational Citizenship Behavior through Job Satisfaction among Public Health Workers - Ahmad Zakie; Dedi Muhammad Siddiq; Mazlina Mamat; Prattana Srisuk (Fakultas Ekonomika dan Bisnis Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to examine the influence of altruistic leadership and empowering leadership to Organizational Citizenship Behavior (OCB) through job satisfaction. A quantitative associative approach was used, based on Structural Equation Modeling-Partial Least Squares (SEM-PLS), and the analysis was conducted using SmartPLS 4. The sample included 146 employees who were chosen from a total group of 230 employees working at four health centers. The findings show that Altruistic Leadership and Empowering Leadership both have a positive and meaningful impact on Job Satisfaction and OCB. Job satisfaction also has a positive effect on OCB and plays a major role in how the two leadership styles connect with OCB. The model accounts for 54.8% of the variation in job satisfaction and 68.6% in organizational citizenship behavior. These results back up the idea of Social Exchange Theory, showing that when leaders act in a positive way, employees are more likely to go beyond their regular job duties in return. This study helps improve how leadership is understood and how people are managed in healthcare settings that provide primary care.